2384. Multidrug-Resistant Gram-Negative Infections Treated With Ceftolozane–Tazobactam: Impact of Delayed Initiation. (26th November 2018) - Jorgensen, Sarah; Trinh, Trang D; Zasowski, Evan J; Lagnf, Abdalhamid M; Bhatia, Sahil; Simon, Samuel; Estrada, Sandy; Rosenberg, Joshua; Steed, Molly; Davis, Susan L; Rybak, Michael J
Abstract: Background: Delayed appropriate antibiotic therapy for multidrug-resistant (MDR) Gram-negative bacterial (GNB) infections has been associated with increased mortality. Ceftolozane-tazobactam (C/T) is a novel antipseudomonal cephalosporin and β-lactamase inhibitor combination with excellent in vitro activity against MDR GNB, however its ability to improve patient outcomes may be attenuated if initiation is delayed or it is reserved for salvage therapy. We sought to determine the impact of delayed C/T initiation on 30-day mortality in patients with MDR GNB infections. Methods: This was a multicenter, retrospective cohort study including adult patients treated with C/T (≥72 hours) for suspected or confirmed MDR GNB (resistant to ≥1 drug from ≥3 classes) infections between January 2015 and February 2018. Classification and regression tree (CART) analysis was used to determine the time point of C/T initiation from index culture or diagnosis most predictive of 30-day mortality. Clinical characteristics and outcomes were compared between patients receiving early or delayed C/T, defined by the CART time point. Multivariable logistic regression was conducted to determine the independent association between early C/T initiation and 30-day mortality. Results: A total of 144 patients were included. The median (IQR) age was 61 (49, 71) years with a male (65%) and African American (53%) predominance. The most common source of infection was respiratory (64%) and MDR Pseudomonas aeruginosa was isolated from 92% of cultures. A breakpoint in time was identified of 119 hours where 30-day mortality was significantly increased (11.8% vs. 26.2%; P = 0.032). Absence of prior infection or colonization with MDR GNB was the only variable independently associated with delayed C/T ( a OR 3.28, 95% CI 1.53, 7.01). After adjustment for confounding variables, delayed C/T was associated with a > 3-fold increase in 30-day mortality ( a OR 3.22, 95% CI 1.11, 9.40). Conclusion: These data suggest that delaying C/T initiation by approximately 5 days substantially increases the risk of mortality in patients with MDR GNB infections, underscoring the importance of early appropriate therapy and the need for incorporation of C/T into automated susceptibility testing panels to support earlier initiation. Disclosures: S. L. Davis, Achaogen: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. Melinta: Scientific Advisor, Consulting fee. Nabriva: Scientific Advisor, Consulting fee. Zavante: Scientific Advisor, Consulting fee. M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support. Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support.